Comprehensive assessment of tumour budding by cytokeratin staining in colorectal cancer. Issue 7 (2nd March 2017) - Rieger, Gregor; Koelzer, Viktor H; Dawson, Heather E; Berger, Martin D; Hädrich, Marion; Inderbitzin, Daniel; Lugli, Alessandro; Zlobec, Inti
Abstract : Aims: Tumour budding in colorectal cancer (CRC) is a recognized prognostic parameter. The aim of this study was to address the use of cytokeratin immunostaining for the visualization and scoring of tumour buds. Methods and results: Ten hotspots (0.238 mm 2 ) of peritumoural budding (PTB) and intratumoural budding (ITB) were evaluated in surgical resections from 215 patients. The budding counts in the 10 densest regions anywhere in the tumour were combined into an overall tumour budding (OTB) score. The PTB, ITB and OTB hotspot with the maximum budding count was then evaluated. Finally, continuous and cut‐off values of 10 buds per high‐power field (HPF) (PTB10HPF ), five buds per HPF (ITB10HPF ) and eight buds per HPF (OTB10HPF ) were used to categorize budding counts into low‐grade and high‐grade scores. All budding scores were highly correlated. PTB and ITB counts were associated with many clinicopathological features, including tumour stage, lymph node and distant metastasis, venous and lymphovascular invasion, and disease‐free survival (DFS) (all P  < 0.05). Analyses of OTB counts recapitulated these associations, including a lower DFS with a greater number of tumour buds ( P  = 0.0309; hazard ratio 1.0332, 95% confidence interval 1.003–1.062). One OTB hotspot performed similarly to 10 OTB hotspots in terms of relationship with outcome. These statistical significances were largely lost when cut‐offs were applied to PTB, ITB or OTB counts. Conclusions: An OTB count in a single hotspot on cytokeratin‐stained CRC tissue sections is a fast and reliable prognostic scoring system for the assessment of tumour budding. This approach should be considered in future studies.